Development of in-line fiber-optic interferometric sensors by using biopolymer : chitosan. - Chen, Li Han. (2013)
In recent years, polymers have increasingly been utilized and studied as possible waveguide materials. The reason for this trend is attributed to the advantages that polymers possess, such as the ease of structure modification, high structural integrity, excellent biocompatibility, good optical and mechanical properties. Among all the polymeric materials, chitosan which is a natural polymer, is one of the most promising candidates to be used as a sensitive medium for optical sensors in various sensing applications, and it is the subject of this thesis. This study explores possibilities of designing chitosan to possess versatile sensing response and integrating it into in-line fiber-optic interferometric sensors for acoustic, humidity and biosensing applications.